2008
DOI: 10.1080/10717540802006674
|View full text |Cite
|
Sign up to set email alerts
|

The Delivery of Platinum Drugs from Thermosensitive Hydrogels Containing Different Ratios of Chitosan

Abstract: New thermosensitive hydrogels of poly(N-isopropylacrylamide) (PNIPAAm) with chitosan (CPN) were prepared and evaluated for use in the delivery of the platinum drugs, cisplatin and carboplatin. The effects of polymers containing different ratios of chitosan on the physicochemical and drug release characteristics were examined. The sol-gel transition temperature of the hydrogels was determined by differential scanning calorimetry (DSC) and viscometry. Discrepancies in the transition temperature among the various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 38 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…. The cumulative release results in general compares well to previous cisplatin encapsulated drug delivery systems (Cheng et al, ; Czarnobaj & Lukasiak, ; Fang, Chen, Leu, & J‐W, ; Guven et al, ; Reardon et al, ). Guven et al () reported less than 25% total released cisplatin from their Pluronic ® F108‐wrapped, W‐CDDP@US‐tubes after 200 h. Cheng et al () reported less than 10% total cisplatin release from their Fe‐cisplatin loaded nanoparticles, Pt‐PHNPs, at pH 7.4, 6, and 5 after 70 h. Reardon et al () reported less than 20% cumulative release of cisplatin after 10 h from their core‐shell poly(lactic‐ co ‐glycolic acid) (PLGA) nanoparticles.…”
Section: Resultssupporting
confidence: 82%
“…. The cumulative release results in general compares well to previous cisplatin encapsulated drug delivery systems (Cheng et al, ; Czarnobaj & Lukasiak, ; Fang, Chen, Leu, & J‐W, ; Guven et al, ; Reardon et al, ). Guven et al () reported less than 25% total released cisplatin from their Pluronic ® F108‐wrapped, W‐CDDP@US‐tubes after 200 h. Cheng et al () reported less than 10% total cisplatin release from their Fe‐cisplatin loaded nanoparticles, Pt‐PHNPs, at pH 7.4, 6, and 5 after 70 h. Reardon et al () reported less than 20% cumulative release of cisplatin after 10 h from their core‐shell poly(lactic‐ co ‐glycolic acid) (PLGA) nanoparticles.…”
Section: Resultssupporting
confidence: 82%
“…Our present report aims at the synthesis of CPN and HA-CPN copolymers based on the combination of PNIPAM-COOH, chitosan and HA in the presence of water-soluble EDC/NHS. CPN is a comb-like copolymer with PNIPAM side chain extending from the chitosan backbone [22,23]. The double grafted HA-CPN was synthesized by grafting CPN onto the HA molecules [24,25].…”
Section: Synthesis Of Cpn and Ha-cpn Copolymersmentioning
confidence: 99%
“…Previously, we reported the synthesis of chitosan-g-poly(Nisopropylacrylamide) (CPN), a thermo-responsive comb-like polymer with chitosan as the backbone and pendant PNIPAM groups, by grafting PNIPAM-COOH with a single carboxyl end group onto chitosan through amide bond linkages [22,23]. In vitro cell culture experiments demonstrated usefulness of this hydrogel as an injectable cell carrier [22].…”
Section: Introductionmentioning
confidence: 97%
“…PNIPAAm has the property of having a soluble (hydrophilic)–insoluble (hydrophobic) transition at a lower critical solution temperature (LCST) of about 32°C in water; it exhibits a coil (soluble) state when the temperature is below the LCST and a collapsed (insoluble) state when the temperature is above the LCST . Moreover, PNIPAAm is also among the smart polymers most commonly used to modify nanoparticles in drug‐delivery systems . The thermally responsive behavior of PNIPAAm can be used to design a smart nanoshell on the exterior surface of MSNs; this may be the ideal way to take up and control the release of drugs based on temperature changes.…”
Section: Introductionmentioning
confidence: 99%